Comportamento sedentário, atividade física e estado nutricional de idosos - CAMILO, Bruno de Freitas (2017)
From the epidemiological transition that has occurred in recent decades, there is a change in the age pyramid, with the increasing population of elderly. In addition, there is a change in the lifestyle of the individuals in relation to eating habits, reduction of the practice of physical activities and increase of the time in sedentary behavior. So, there is the need to understand the relationship between these variables and their deleterious effects on the health of individuals. Therefore, the objective of this study was to analyze the association of sedentary behavior and level of physical activity in a combined and independent way with nutritional status in the elderly. In the first article, a systematic review was performed on the BVS, PubMed and Web of Science databases to analyze observational studies that evaluated the association between exposure time to sedentary behavior and nutritional status (overweight/malnutrition) in individuals of age ≥60 years. Eight articles were included in the systematic review with meta-analysis that demonstrated that longer exposure to sedentary behavior did not increase the odds of overweight and / or obesity in the elderly. In the second article, was to investigate the association between sedentary behavior and level of physical activity in combination and independent with overweight and obesity in the elderly living in a region of northeastern Brazil. This cross-sectional study, which is an integral part of the Elderly's Health Longitudinal Study of Alcobaça - ELSIA, was performed in 452 individuals aged ≥60 years. A structured questionnaire containing sociodemographic and behavioral information was applied. Sedentary behavior was assessed through self-report. Overweight and obesity were measured using the body mass index. The multinomial regression was used to evaluate the association between sedentary behavior and level of physical activity with overweight and obesity. In the crude analysis, there was an association between sex, smoking and consumption of medicines with overweight and obesity. After the adjustment, there was no association between the variables in the analyses performed independently and combined. It is suggested that new studies with standardized criteria for measuring sedentary behavior and overweight and obesity be performed in order to understand the relationship between these variables